KETEPATAN PEMAKAIAN EJAAN YANG DISEMPURNAKAN DALAM SKRIPSI MAHASISWA PRODI PENDIDIKAN LUAR SEKOLAH FKIP UNIVERSITAS RIAU - Dahlia Dahlia; Auzar Auzar; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the Accuracy of Improved Spelling Use in Student Thesis of Faculty of Teachers Training and Education, University outside Education Study Program. This study aims to describe the Accurate Spelling Use Accuracy in the thesis of Student Education outside Education, Faculty of Teachers Training and Education University of Riau. The method used is descriptive method. In this study, the authors used three techniques namely reading, observing, marking techniques. In this research, there are 27 theses, from the results of search that the authors found in the Thesis of Student Education Outside Education Faculty of Teachers Training and Education, University of Riau. The study found that there are 281 inaccuracy of capital letter usage and 119 inaccuracy use of the letter in an enhanced spelling.Keywords: Accurate Spelling Use Acuracy, Thesis of Student, of Outside School Education.